Étude sur les besoins spécifiques des femmes immigrantes francophones en situation minoritaire - Alliance des femmes de la francophonie canadienne (L’Alliance des femmes de la francophonie canadienne (AFFC), 2021)

Stratégies d’intégration et de support en santé mentale des immigrants francophones au Canada anglais. - Archambault, Hélène; de Moissac, Daniel; Tempier, Raymond (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Résumé Cet article explore les stratégies d’intégration au système de santé telles que proposées par des personnes immigrantes francophones au sein de communautés francophones en situation minoritaire au Canada (CFSM). Une recherche qualitative par entrevues semi-dirigées a été menée dans trois villes canadiennes auprès de soixante personnes adultes immigrantes ou réfugiées. Centrées sur les représentations des personnes immigrantes quant aux services de soutien en santé mentale, diverses stratégies ont été dégagées. La préparation prémigratoire et le regroupement des informations sous un guichet unique semblent contribuer à une intégration réussie. L’appui des organismes communautaires et des autorités religieuses est bénéfique pour le soutien informationnel et socioémotionnel des nouveaux arrivants, ayant des retombées positives sur leur bien-être et leur capacité de s’intégrer à leur nouveau milieu de vie. Mots-clés : immigration, francophones, intégration, système de santé, stratégies Abstract This article explores healthcare integration strategies proposed by Francophone immigrants within Francophone minority communities (FMCs) in Canada. A qualitative study using semi-structured interviews was conducted in three Canadian cities with sixty adult immigrants and refugees. Focusing on immigrants’ perceptions of mental health support services, various strategies were identified. Pre-migration preparation and centralizing information seem to contribute to successful integration. The support of community organizations and religious authorities is beneficial for the socio-emotional and information support of newcomers, having a positive impact on their well-being and their ability to integrate into their new living environment. Keywords: immigration, Francophones, integration, healthcare, strategies

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Distance, access and equity: A cross-sectional geospatial analysis of disparities in acess to primary care for French-only speakers in Ottawa, Ontario - Belanger, Christopher; Carr, Kady; Peixoto, Cayden; Bjerre, Lise M. (CMAJ Open, 2023)
Background: Although language concordance between patients and primary care physicians results in better quality of care and health outcomes, little research has explored inequities in travel burden to access primary care people of linguistic minority groups in Canada. We sought to investigate the travel burden of language-concordant primary care among people who speak French but not English (French-only speakers) and the general public in Ottawa, Ontario, and any inequities in access across language groups and neighbourhood ruralities. Methods: Using a novel computational method, we estimated travel burden to language-concordant primary care for the general population and French-only speakers in Ottawa. We used language and population data from Statistics Canada’s 2016 Census, neighbourhood demographics from the Ottawa Neighbourhood Study, and collected the main practice location and language of primary care physicians from the College of Physicians and Surgeons of Ontario. We measured travel burden using Valhalla, an open-source road-network analysis platform. Results: We included data from 869 primary care physicians and 916 855 patients. Overall, French-only speakers faced greater travel burdens than the general population to access language-concordant primary care. Median differences in travel burden were statistically significant but small (median difference in drive time 0.61 min, p < 0.001, interquartile range 0.26–1.17 min), but inequities in travel burden between groups were larger among people living in rural neighbourhoods.

Étude sur les populations âgées et l’accès aux soins de longue durée en français en Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)
Ce rapport présente une analyse de la demande et de l’offre de services de santé en français (SSF) dans le secteur des soins de longue durée (SLD) en Ontario. En nous appuyant sur des données publiques ainsi que sur des données administratives fournies par le ministère de la Santé de l’Ontario, le rapport examine : 1. la demande régionale de SSF, évaluée selon la population ontarienne âgée de 65 ans et plus et la population francophone de ce groupe d’âge ; 2. l’offre de SSF, mesurée par le nombre et le type de foyers présents dans chaque région, ainsi que par les compétences linguistiques en français de leur personnel.

Study of aging populations and access to French-language long-term care in Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)

Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes - Bouchard, Louise; Batista, Ricardo; Reaume, Michael (Université d’Ottawa et Institut du savoir Montfort, 2021)
fs-ref-orig: Bouchard, L., Batista, R. et Reaume, M. (2021). Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes. Université d’Ottawa et Institut du savoir Montfort. fs-code-orig: Bouchard-2021a

L'offre active de services de santé mentale en français en Ontario et au Manitoba : les rôles clés des instruments et des outils - Cardinal, Linda; de Moissac, Danielle; Deschênes-Thériault, Guillaume (Administration publique du Canada / Canadian Public Administration, 2023)
Cet article présente les données d'un sondage réalisé en 2019 sur la connaissance des gestionnaires et des professionnels œuvrant dans le domaine de la santé mentale en Ontario et au Manitoba de leurs obligations linguistiques et des outils qui favorisent la pratique de l'offre active de services français. L'étude permet de souligner que plus les professionnels et les gestionnaires comprennent leurs obligations, tant en Ontario qu'au Manitoba, plus ils peuvent profiter des outils existants pour s'en acquitter. L'étude montre qu'il existe en effet un lien entre la connaissance des obligations et l'utilisation des outils pour faire de l'offre active de services de santé mentale en français. Elle permet aussi d'insister sur le rôle clé des outils pour faire de l'offre active de services en français.

Évaluer le potentiel de soins linguistiquement concordants pour les francophones de l’Ontario : une étude populationnelle transversale. - Carr, Kady; Batista Moliner, Ricardo; Fitzgerald, Michael; Lamontagne, Sophie; Bader Eddeen, Anan; Timony, Patrick E.; Bédard, Daniel; Gauthier, Alain; Prud’homme, Denis; Landry, Josette-Renée; Chomienne, Marie-Hélène; Denis-Leblanc, Manon; et al. (Minorités linguistiques et société, 2024)
Cette étude a utilisé les données sur les médecins, la facturation et le recensement de 2016 dont dispose l’ICES pour examiner l’accès potentiel à des médecins de famille francophones pour les francophones résidant dans 1 643 aires de diffusion agrégées (ADA) de l’Ontario. L’Ontario compte 550 280 francophones, soit 4,1 % de sa population. Nous avons identifié 8 199 médecins de famille, parmi lesquels 1 169 se sont autodéclarés francophones. Le ratio provincial global pour les francophones était de 2,12 médecins par 1 000 résidentes et résidents, comparativement à un ratio de 0,66 pour les anglophones. Dans les ADA où les francophones étaient majoritaires, le ratio pour les francophones était inférieur au ratio pour les anglophones (0,63 vs 2,02), alors que dans toutes les autres ADA, le ratio francophone était plus élevé (3,46 vs 0,62 dans les 83,4 % des ADA où les francophones représentaient >0 % à <5 % de la population). Huit ADA du Nord-Est et de l’Est de l’Ontario présentaient un déficit relatif important de médecins de famille francophones par rapport au ratio provincial. Ces résultats donnent un aperçu des régions qui pourraient bénéficier de programmes visant à éliminer les barrières linguistiques. Mots-clés : Concordance linguistique, médecins de famille, accès aux soins primaires, francophones, Ontario

Le moment Monfort dans la francophonie canadienne. - Charbonneau, François (Presses de l’Université d’Ottawa, 2024)

Perceptions des professionnels de la santé quant aux besoins oncologiques pédiatriques offerts en français à domicile : étude descriptive qualitative - Chartrand, Julie; Jibb, Lindsay; Grandmont, Camille; Hardy-Bélanger, Élisabeth; Cheng, Sara; Balasa, Rebecca; Johnston, Donna (Revue canadienne de soins infirmers en oncologie, 2022)

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Coup d’œil sur la recherche : Qualité et sécurité des soins de longue durée en Ontario [infographie] - Consortium national de formation en santé; van Kemenade, Solange (2022)
fs-ref-orig: Consortium national de formation en santé et van Kemenade, S. (2022). Coup d’œil sur la recherche : Qualité et sécurité des soins de longue durée en Ontario. fs-code-orig: Consortium national de formation en santé-2022b

Management strategies to improve French language service coordination and continuity for official language Francophone seniors in Canada - de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Kubina, Lucy-Ann (Healthcare Management Forum, 2020)
Evidence suggests that language barriers present obstacles to healthcare access and quality for Francophone seniors in official language minority communities across Canada. Addressing language barriers and providing continuity is challenging, as French language services (FLSs) rely heavily on bilingual providers and the practice of active offer by all staff. This qualitative research used semi-structured group and individual interviews to explore mechanisms supporting FLS coordination and continuity in two Canadian provinces. Identification of the language variable in health records, virtual healthcare, and FLS directories are conducive to FLS continuity, but financial and resource limitations present major obstacles. Management strategies to facilitate continuity of FLS across health organizations are discussed.

Barriers in accessing HIV care for Francophone African, Caribbean and Black people living with HIV in Canada: A scoping review - Djiadeu, Pascal; Yusuf, Abban; Ongolo-Zogo, Clémence; Nguemo, Joseph; Odhiambo, Apondi J.; Mukandoli, Chantal; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2020)
Introduction In 2001, 50%–55% of French-speaking minority communities did not have access to health services in French in Canada. Although Canada is officially a bilingual country, reports indicate that many healthcare services offered in French in Anglophone provinces are insufficient or substandard, leading to healthcare discrepancies among Canada’s minority Francophone communities. Objectives The primary aim of this scoping systematic review was to identify existing gaps in HIV-care delivery to Francophone minorities living with HIV in Canada. Study design Scoping systematic review. Data sources Search for studies published between 1990 and November 2019 reporting on health and healthcare in Francophone populations in Canada. Nine databases were searched, including Medline, Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, the National Health Service Economic Development Database, Global Health, PsychInfo, PubMed, Scopus and Web of Science. Study selection English or French language studies that include data on French-speaking people with HIV in an Anglophone majority Canadian province. Results The literature search resulted in 294 studies. A total of 230 studies were excluded after duplicates were removed. The full texts of 43 potentially relevant papers were retrieved for evaluation and data extraction. Forty-one studies were further excluded based on failure to meet the inclusion criteria leaving two qualitative studies that met our inclusion criteria. These two studies reported on barriers on access to specialised care by Francophone and highlighted difficulties experienced by healthcare professionals in providing quality healthcare to Francophone patients in Ontario and Manitoba. Conclusion The findings of this scoping systematic review highlight the need for more HIV research on linguistic minority communities and should inform health policymaking and HIV/AIDS community organisations in providing HIV care to Francophone immigrants and Canadians.

Vers une amélioration de la prestation de services de santé pour les Franco-Ontariens - Doucet, Pascale-Anne. M.; Gorham, Robyn; Hunt, Elena (Journal de recherche interdisciplinaire, 2021)
Malgré le statut de dualité linguistique du Canada, la communauté francophone continue d’être laissée pour compte par les autorités du pays. Plus spécifiquement, l’étendue et l’accès restreints des services de santé offerts aux francophones en Ontario posent un grave danger pour cette population. Les établissements qui dispensent des services de santé continuent d’ignorer les politiques de soins existantes. Cette situation impose plusieurs actions au niveau fédéral, législatif et communautaire nécessaires afin d’assurer la garantie bilingue promise à la population canadienne. Parmi celles-ci, il faut augmenter la présence francophone dans les groupes décisionnels pour assurer la conception et l’établissement de programmes et services de santé axés sur les besoins uniques et distincts des franco-ontariens. Par ailleurs, l’engagement financier fédéral envers des organismes communautaires francophones est essentiel afin de fournir plus de services de santé en français, surtout dans les communautés nordiques et rurales de la province. Finalement, la subvention gouvernementale de futures recherches sur la santé des francophones est nécessaire puisque celles-ci vont servir de base solide pour déterminer comment mieux desservir cette population. Pour y arriver, il faudrait considérer le lobbying, l’encouragement des institutions qui dispensent des services de santé d’obtenir leur désignation bilingue, et la mise à jour de la Loi sur les services en français. Cependant, en continuant l’inaction, les Franco-Ontariens risquent de devenir assimilés au restant de la population, de dépérir et de voir leur santé se détériorer. Cet article cherche notamment à signaler la nécessité d’améliorer la prestation de services de santé en français en Ontario.

mobilisation collective pour une santé en français en ontario. closm santé - Forest, Mariève; Gilbert, A.; Bouchard, Louise (Le moment Monfort dans la francophonie canadienne, 2024)

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

L'effectivité des lois linguistiques dans le secteur de la santé. Rapport - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Sommaire - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

Practice #28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario) - Ibrahim, Nour; Benoît, Josée; Savard, Jacinthe (2025)
fs-ref-orig: Ibrahim, N., Benoît, J. & Savard, J. (2025). Practice 28: Access to Resources in the Community (ARC): A social prescribing and navigation model (Ontario). In: GReFoPS. Directory of Innovative Practices in Health and Social Services in Official Language Minority Contexts. https://www.grefops.ca/directory_ innovative_practices.html fs-code-orig: Ibrahim-2025

Recrutement de prestataires de services maîtrisant le français : conseils et stratégies - Institut du savoir sur la santé mentale et les dépendances chez les enfants et les jeunes (2023)

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

La première étape de la validation transculturelle des versions anglophones des tests de l'horloge et du Mini-Mental pour mesurer les capacités cognitives des Franco-Ontariens âgés de plus de 65 ans - Larocque, Sylvie; Lavoie, Anne-Marise; Omri, Nadia (Reflets, 2021)
La maladie d’Alzheimer est un syndrome neurodégénératif chronique caractérisé par un déclin cognitif et mnésique. Les personnes atteintes par cette maladie développent des affections rattachées à la langue. Il est important de faire passer des tests de dépistage dans la langue maternelle de la personne puisque l’aptitude linguistique décline avec la progression de la maladie. De manière générale, le Mini-mental et le test de l’horloge sont administrés en anglais aux francophones du nord de l’Ontario ce qui peut mener à une sous-évaluation de leurs capacités cognitives et à un diagnostic erroné. Voilà pourquoi le but de cette recherche était de développer et valider les tests psychométriques francophones administrés aux Franco-Ontariens. Le Mini-mental et le test de l’horloge ont été traduits selon la validation transculturelle de Caron (1999) et testés auprès des francophones du Grand Sudbury qui souffraient de déficits cognitifs (N=14). Aucune différence statistique (p>.05) entre les scores de la traduction franco-ontarienne du test de l’horloge et du Mini-mental comparés aux tests originaux n’a été détectée. Bien que d’autres recherches soient nécessaires, selon les auteures, ces traductions permettront d’assurer un dépistage juste de cette maladie chez les francophones âgés en situation minoritaire. Mots-clés : dépistage d’Alzheimer, Mini-mental de Folstein, test de l’horloge, traduction transculturelle

Exploring Primary Care Physicians’ Experiences of Language and Cultural Discordant Care for Linguistic Minority Patients at the End-of-Life: A Study Protocol - Lee, Seung Heyck; Gibb, Maya; Karunananthan, Sathya; Cody, Margaret; Tanuseputro, Peter; Johnston, Sharon; Kendall, Claire; Bedard, Daniel; Collin, Stéphanie; Kehoe MacLeod, Krystal (International Journal of Qualitative Methods, 2023)
Health disparities exist across different linguistic groups. Language barriers in primary care can negatively affect access to healthcare services and the quality and safety of care at the end-of-life. This study will take a novel, in-depth look at the experience of language- and/or cultural-discordant care for adults from linguistic minority groups through the eyes of primary care physicians providing palliative and/or end-of-life care. Language and cultural discordance means that the physician and patient do not speak the same language or are not from the same cultural background. Qualitative data from primary care physicians (n = 12–24) providing language-discordant end-of-life care to Francophone and/or Allophone older adults across different care models and diverse geographies in Ontario will be collected through semi-structured interviews. Reflexive thematic analysis will be used to report themes within the data and consider the influence of the social locations of the researcher and research participants, geographic considerations impacting service provision, and barriers imposed by differing primary care funding structures on the provision of palliative and end-of-life care for linguistic and cultural minority groups in Ontario. Findings from this study will identify the interconnections among language and cultural discordance, care model, geographic region, and physician perceptions of their combined effects on access to, and quality of, palliative and end-of-life care. This evidence will be key to informing clinical practice guidelines and mobilizing change to improve primary care access and quality for adults at the end-of-life from linguistic and cultural minority populations across Ontario. Keywords: language discordance, qualitative research, reflexive thematic analysis, palliative care, primary care physicians, semi-structured interviews

Accès aux soins de longue durée dans la région d'Érié St. clair : Analyse et recommandation - Mian, Guy (Entité de planification des services de santé en français Érié St.Clair/Sud-Ouest, 2021)
Ce rapport a été préparé dans le cadre du Plan d’Action Conjoint 2019-2022 du RLISS-Entité,¹ où les soins et les services aux aînés sont considérés comme prioritaires et, en particulier, l’accès aux soins de longue durée (SLD) dans la région d’Érié St. Clair. Le présent rapport vise à formuler des recommandations à l’intention de Santé Ontario (SO) Ouest afin de combler les lacunes en matière d’accessibilité aux soins de longue durée (SLD) en français et, par conséquent, dans les services de soutien à domicile et en milieu communautaires (SSDMC) afin de maintenir les aînés francophones à domicile dans la région d’Érié St. Clair (ESC). Dans la mesure du possible, le rapport proposera également des recommandations pour la localité de London dans la région du Sud-Ouest (S-O).

Official Language Minority Communities in Ontario: Understanding the Lived Experiences of Francophone Patients and their Nursing Care Providers - Muray, Mwali (2022)
Although Canada is a bilingual country, official language minority community patients struggle to access quality care in their language. This reality has been of concern for Francophone minority communities in Ontario, but has seldom been examined in a nursing context. This research sought to examine the lived experiences of registered nurses and nursing students providing care to French-speaking patients in Ontario, as well as the realities of Francophone patients seeking French language health care services in Ontario. The conceptual frameworks guiding the study were the “Four Levels of Change for Improving Quality” model and the “Four-Level Model of the Health Care System.” Using qualitative phenomenological inquiry, as influenced by Martin Heidegger and Max van Manen, 31 semi-structured interviews were conducted with three subsets (n=10 Francophone patients; n=10 nursing students; n=11 registered nurses) throughout Ontario who had experience with the phenomenon being investigated. Data collection took place over a year (2018-2019) and was analysed thematically. Significant findings were identified across the three groups. Participants revealed the patchwork of individual actions taking place to remedy the existing gaps regarding care for Francophone minority populations. This included navigating a health care system where good enough care was the unfortunate standard for Francophone patients, and discussing how Francophone patients and nursing care providers implement strategies individually to manage the lack of resources for Francophone patient populations in Ontario. This thesis asserts that official language minority communities and their nursing care providers remain faced with difficulties providing and receiving care in Ontario. While numerous structures and resources exist to remediate the problems, these interventions and resources are not always implemented systemically, leading to a disproportionate burden on individuals, significant risks for safety for patient populations, and ethical dilemmas for nursing care providers. Recommendations are provided to bridge the gaps and ensure considerations of the needs of linguistic minorities throughout the health care system. Keywords: Francophonie, Linguistic Minorities, Nursing, Phenomenology, Qualitative Research

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada. - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.

Problèmes d’accès aux services en français ? Contactez-nous. Nous pouvons vous aider [infographie] - Ombudsman de l'Ontario (2022)

Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication] - Ontario mental health & addictions virtual care collaborative (Centre for Addiction and Mental Health (CAMH), 2021)
fs-ref-orig: Ontario mental health & addictions virtual care collaborative. (2021). Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication]. Centre for Addiction and Mental Health (CAMH). fs-code-orig: Ontario mental health & addictions virtual care collaborative-2021

Problems accessing services in French? Contact us. We can help [infographie] - Ontario Ombudsman (2022)

The impact of language on emergency department visits, hospitalizations, and lenght of stay among home care recipients - Reaume, M.; Batista, Ricardo; Rhodes, Emily; Knight, Braden; Imsirovic, Haris; Seale, Emily; Riad, Karine; Prud'homme, Denis; Tanuseputro, Peter (Medical care, 2021)
Background: Research considering the impact of language on health care utilization is limited. We conducted a population-based study to: (1) investigate the association between residents’ preferred language and hospital-based health care utilization; and (2) determine whether this association is modified by dementia, a condition which can exacerbate communication barriers. Methods: We used administrative databases to establish a retrospective cohort study of home care recipients (2015–2017) in Ontario, Canada, where the predominant language is English. Residents’ preferred language (obtained from in-person home care assessments) was coded as English (Anglophones), French (Francophones), or other (Allophones). Diagnoses of dementia were ascertained with a previously validated algorithm. We identified all emergency department (ED) visits and hospitalizations within 1 year. Results: Compared with Anglophones, Allophones had lower annual rates of ED visits (1.3 vs. 1.8; P<0.01) and hospitalizations (0.6 vs. 0.7; P<0.01), while Francophones had longer hospital stays (9.1 vs. 7.6 d per admission; P<0.01). After adjusting for potential confounders, Francophones and Allophones were less likely to visit the ED or be hospitalized than Anglophones. We found evidence of synergism between language and dementia; the average length of stay for Francophones with dementia was 25% (95% confidence interval: 1.10–1.39) longer when compared with Anglophones without dementia. Conclusions: Residents whose preferred language was not English were less frequent users of hospital-based health care services, a finding that is likely attributable to cultural factors. Francophones with dementia experienced the longest stays in hospital. This may be related to the geographic distribution of Francophones (predominantly in rural areas) or to suboptimal patient-provider communication.

Linguistic factors and COVID-19 outcomes among long-term care residents in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Imsirovic, Haris; Bjerre, Lise; Kendall, Claire E.; Bouchard, Louise; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Hélène; Muray, Mwali; Hsu, Amy; Prud'homme, Denis; et al. (BMC Geriarics, 2025)
Abstract Background The COVID-19 pandemic disproportionately affected frail individuals, especially those living in long-term care (LTC) homes. This study examined the role of linguistic factors on COVID-19 related outcomes in LTC homes. Methods We performed a population-based, retrospective cohort study of residents living in LTC homes in Ontario, Canada who were diagnosed with COVID-19 between March 31, 2020 and March 31, 2021. Resident language, obtained from LTC assessments, was used to classify residents into one of the three linguistic groups: Anglophone (English), Francophone (French), and allophone (other language). Language of the LTC home was determined using a person-time representation of the languages spoken by residents within each LTC home. We defined LTC facilities as French homes when Francophone residents contributed more than 25% of the person-days, and allophone homes when allophone residents contributed more than 50% of the person-days. Residents whose language corresponded to the language of the LTC home in which they were living were said to have received language-concordant care, while all other residents were said to have received language-discordant care. The outcomes of this study were ED visits, hospitalizations, and mortality within 90 days. Results We included a total of 26,829 LTC residents (20,315 Anglophones, 1,032 Francophones, and 5,482 allophones) living in 572 LTC homes (502 English, 28 French, 42 allophone) who were diagnosed with COVID-19. LTC residents who lived in language-discordant homes were more likely to have ED visits (adjusted HR 1.12, 95% CI 1.01–1.25) and hospitalizations (adjusted HR 1.15, 95% CI 1.02–1.29) when compared to LTC residents who lived in language-concordant homes. Residents-facility language discordance was not associated with overall mortality (adjusted HR 1.00, 95% CI 0.91–1.10) or in hospital mortality (adjusted HR 1.04, 95% CI 0.88–1.23). Conclusion Residents living in language-discordant LTC facilities experienced more ED visits and hospitalizations following diagnosis of COVID-19. The findings of this study highlight the importance of providing frail, vulnerable individuals with linguistically concordant care.

Qualité et sécurité des services de santé offerts en situation linguistique minoritaire en Ontario : investigations des données administratives de santé. - Reaume, Michael; Batista, Ricardo; Prud’homme, Denis; Tanuseputro, Peter (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons une synthèse de plusieurs analyses récentes réalisées par notre groupe de recherche à partir de données administratives de santé pour mesurer la qualité et la sécurité des services de santé offerts aux francophones et allophones en Ontario, Canada. Les résultats de nos analyses démontrent que les Ontariennes et les Ontariens qui reçoivent des soins dans leur principale langue d’usage ont généralement de meilleurs résultats cliniques comparés à ceux qui reçoivent des soins dans une langue autre que leur principale langue d’usage. Ceci suggère que la qualité et la sécurité des soins offerts aux patients et aux patientes en situation de discordance linguistique pourraient être améliorées par le pairage de professionnel-patient parlant la même langue, par exemple, en référant un patient à un médecin qui parle la langue du patient, ou en s’assurant que les francophones ont accès aux services en français en milieux désignés en Ontario en vertu de la Loi sur les services en français et que les allophones puissent bénéficier de davantage de services d’interprétariat. Mots-clés : allophones, données administratives de santé, francophones, minorités de langue officielle, minorités linguistiques, qualité et sécurité des soins de santé

Impact of patient–family physician language concordance on healthcare utilisation and mortality: A retrospective cohort study of home care recipients in Ontario, Canada. - Reaume, Michael; Batista, Ricardo; Sucha, Ewa; Pugliese, Michael; Roberts, Rhiannon; Rhodes, Emily; Seale, Emily; Kendall, Claire. E.; Bjerre, Lise; Bouchard, Louise; Johnson, Sharon; Sood, Manish; et al. (BMJ Public Health, 2024)
Introduction As the world’s linguistic diversity continues to increase at an unprecedented rate, a growing proportion of patients will be at risk of experiencing language barriers in primary care settings. We sought to examine whether patient–family physician language concordance in a primary care setting is associated with lower rates of hospital-based healthcare utilisation and mortality. Methods We conducted a population-based retrospective cohort study of 497 227 home care recipients living in Ontario, Canada. Patient language was obtained from home care assessments while physician language was obtained from the College of Physicians and Surgeons of Ontario. We defined primary care as language concordant when patients and their rostered family physicians shared a mutually intelligible language, and we defined all other primary care as language discordant. The primary outcomes were Emergency Department (ED) visits, hospitalisations and death within 1 year of index home care assessment. Results Compared with non-English, non-French speakers who received language-discordant primary care, those who received language-concordant primary care experienced fewer ED visits (53.1% vs 57.5%; p<0.01), fewer hospitalisations (35.0% vs 37.6%; p<0.01) and less mortality (14.4% vs 16.6%; p<0.01) during the study period. In multivariable regression analyses, non-English, non-French speakers had lower risks of ED visits (adjusted hazard ratio [aHR] 0.91, 95% CI 0.88 to 0.94), hospitalisations (aHR 0.94, 95% CI 0.90 to 0.98) and death (aHR 0.87, 95% CI 0.82 to 0.93) when they received language-concordant primary care. For francophones, the risk of experiencing an ED visit, a hospitalisation or death was not impacted by the language of their family physician. Conclusions Patient–family physician language concordance is associated with a lower risk of adverse outcomes in non-English and non-French speakers. Optimising the delivery of language-concordant care could potentially result in significant decreases in the use of acute healthcare services and mortality at the population level.

In-hospital patient harm across linguistic groups: A retrospective cohort study of home care recipients - Reaume, Michael; Batista, Ricardo; Talarico, Robert; Guerin, Eva; Rhodes, Emily; Carson, Sarah; Prud'homme, Denis; Tanuseputro, Peter (Journal of patient safety, 2022)
Objective Research examining the impact of language barriers on patient safety is limited. We conducted a population-based study to determine whether patients whose primary language is not English are more likely to experience harm when admitted to hospitals in Ontario, Canada. Methods We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2010 to 2015) who were subsequently admitted to hospital. Patient language (obtained from home care assessments) was coded as English, French, or other. Harmful events were identified using the Hospital Harm Indicator developed by the Canadian Institute for Health Information. Results We included 190,724 patients (156,186 Anglophones, 5,110 Francophones, and 29,428 Allophones). There was no significant difference in the unadjusted risk of harm for Francophones compared with Anglophones (relative risk [RR], 0.94; 95% confidence interval [CI], 0.87–1.02). However, Allophones were more likely to experience harm when compared with Anglophones (RR, 1.14; 95% CI, 1.10–1.18). The risk of harm was even greater for Allophones with low English proficiency (RR, 1.18; 95% CI, 1.13–1.24). After adjusting for potential confounders, Anglophones and Allophones were equally likely to experience harm of any type, but Allophones more likely to experience harm from infections and procedures. Conclusions Patients whose primary language was not English or French were more likely to experience harm after admission to hospital, especially if they had low English proficiency. For these patients, the risk of harm from infections and procedures persisted in the adjusted analysis, but the overall risk of harm did not.

The impact of hospital language on the rate of in-hospital harm. A retrospective cohort study of home care recipients in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Talarico, Robert; Rhodes, Emily; Guerin, Eva; Carson, Sarah; Prud’homme, Denis; Tanuseputro, Peter (BMC Health Services Research, 2020)
Background Patients who live in minority language situations are generally more likely to experience poor health outcomes, including harmful events. The delivery of healthcare services in a language-concordant environment has been shown to mitigate the risk of poor health outcomes related to chronic disease management in primary care. However, data assessing the impact of language-concordance on the risk of in-hospital harm are lacking. We conducted a population-based study to determine whether admission to a language-discordant hospital is a risk factor for in-hospital harm. Methods We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2007 to 2015) who were admitted to a hospital in Eastern or North-Eastern Ontario, Canada. Patient language (obtained from home care assessments) was coded as English (Anglophone group), French (Francophone group), or other (Allophone group); hospital language (English or bilingual) was obtained using language designation status according to the French Language Services Act. We identified in-hospital harmful events using the Hospital Harm Indicator developed by the Canadian Institute for Health Information. Results The proportion of hospitalizations with at least 1 harmful event was greater for Allophones (7.63%) than for Anglophones (6.29%, p < 0.001) and Francophones (6.15%, p < 0.001). Overall, Allophones admitted to hospitals required by law to provide services in both French and English (bilingual hospitals) had the highest rate of harm (9.16%), while Francophones admitted to these same hospitals had the lowest rate of harm (5.93%). In the unadjusted analysis, Francophones were less likely to experience harm in bilingual hospitals than in hospitals that were not required by law to provide services in French (English-speaking hospitals) (RR = 0.88, p = 0.048); the opposite was true for Anglophones and Allophones, who were more likely to experience harm in bilingual hospitals (RR = 1.17, p < 0.001 and RR = 1.41, p < 0.001, respectively). The risk of harm was not significant in the adjusted analysis. Conclusions Home care recipients residing in Eastern and North-Eastern Ontario were more likely to experience harm in language-discordant hospitals, but the risk of harm did not persist after adjusting for confounding variables.

The impact of patient-facility language discordance on potentially inappropriate prescribing of antipsychotics in long-term care home in Ontario, Canada: A retrospective population health cohort study - Reaume, Michael; Peixoto, Cayden; Pugliese, Michael; Tanuseputro, Peter; Batista, Ricardo; Kendall, Claire. E.; Landry, Josette-Renée; Prud’homme, Denis; Chomienne, Marie-Hélène; Farrell, Barbara; Bjerre, Lise M. (BMC Geriatrics, 2024)
Background Appropriate use of medication is a key indicator of the quality of care provided in long-term care (LTC). The objective of this study was to determine whether resident-facility language concordance/discordance is associated with the odds of potentially inappropriate prescribing of antipsychotics (PIP-AP) in LTC. Methods We conducted a population-based, retrospective cohort study of LTC residents in Ontario, Canada from 2010 to 2019. We obtained resident language from standardized resident assessments, and derived facility language by determining the proportion of residents belonging to each linguistic group within individual LTC homes. Using linked administrative databases, we identified all instances of PIP-AP during a 1-year follow-up period. PIP-AP was defined using the STOPP-START criteria, which have previously been shown to predict adverse clinical events such as emergency department (ED) visits and hospitalizations. The association between linguistic factors and PIP-AP was assessed using adjusted multivariable logistic regression analysis. Results We identified 198,729 LTC residents consisting of 162,814 Anglophones (81.9%), 6,230 Francophones (3.1%), and 29,685 Allophones (14.9%). The odds of PIP-AP of were higher for both Francophones (aOR 1.15, 95% CI 1.08–1.23) and Allophones (aOR 1.11, 95% CI 1.08–1.15) when compared to Anglophones. When compared to English LTC homes, French LTC homes had greater odds of PIP-AP (aOR 1.12, 95% CI 1.05–1.20), while Allophone homes had lower odds of PIP-AP (aOR 0.82, 95% CI 0.77–0.86). Residents living in language-discordant LTC homes had higher odds of PIP-AP when compared to LTC residents living in language-concordant LTC homes (aOR 1.07, 95% CI 1.04–1.10). Conclusion This study identified linguistic factors related to the odds of PIP-AP in LTC, suggesting that the linguistic environment may have an impact on the quality of care provided to residents.

La population francophone au sein de votre équipe Santé Ontario : proposition d’indicateurs clés - Réseau des services de santé en français de l'Est de l'Ontario (2022)
fs-ref-orig: Réseau des services de santé en français de l'Est de l'Ontario. (2022). La population francophone au sein de votre équipe Santé Ontario : proposition d’indicateurs clés [infographie]. fs-code-orig: Réseau des services de santé en français de l'Est de l'Ontario-2022a (PDF à séparer)

Rapport sur l’accès aux soins de longue durée en français dans la région de Champlain. Sommaire - Réseau des services de santé en français de l’Est de l’Ontario (2020)
fs-ref-orig: Réseau des services de santé en français de l’Est de l’Ontario. (2020). Rapport sur l’accès aux soins de longue durée en français dans la région de Champlain. Sommaire. fs-code-orig: Réseau des services de santé en français de l’Est de l’Ontario-2020

Rapport provincial sur les SSEF (données de 2018-2019) - Réseau des services de santé en français de l'Est de l'Ontario; Institut Ozi (2020)
Le projet OZi a pour objectif de colliger et d’analyser des données afin de dresser un portrait de la capacité de SSEF. Cette initiative cherche à pallier le manque de données normalisées afin de permettre une planification efficace et une prise des décisions éclairée. Grâce au portail OZi, les fournisseurs de services de santé (FSS) financés par les RLISS ont fourni des données de référence sur leur capacité en matière de SSEF. Le présent rapport porte sur la deuxième année de collecte de données (année 2018-2019). L’analyse porte sur quatre perspectives : la répartition des FSS, le continuum des services, la conformité en matière de désignation et les ressources humaines.

Je suis insatisfait(e) des services de santé reçus. Que faire ? Comment procéder ? [infographie] - Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada; Société Santé en français (2022)

Boîte à outils virtuelle de soins culturellement adaptés pour les francophones dans les foyers de SLD - Réseau du mieux-être francophone du Nord de l’Ontario (2022)

État des lieux pour le secteur des soins à domicile et en milieu communautiare dans le nord de l'Ontario - Réseau du mieux-être francophone du Nord de l'Ontario (2025)
Le Réseau a entrepris le travail de recenser les capacités actuelles du secteur des soins à domicile et en milieu communautaire dans le Nord de l’Ontario, et ce, afin de mieux appuyer les organismes de soins de santé et ainsi renforcer les capacités du secteur. En effet, cette étude permettra au Réseau de connaître les capacités actuelles en termes de professionnels de la santé qui parlent le français dans le Nord de l’Ontario, puis d’identifier les domaines et les régions où les disparités sont plus importantes. Ce rapport pourra servir de guide envers l’établissement des priorités et de stratégies régionales en matière de services en français pour le secteur des soins à domicile et en milieu communautaire.

Recommandations de l’étude de besoins sur les foyers de soins de longue durée du Nord de l’Ontario - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)

Recommendations from the Northern Ontario Long-Term Care Homes Needs Study - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)

The impact of dementia and language on hospitalizations: A retrospective cohort of long-term care residents - Riad, Karine; Webber, Colleen; Batista, Ricardo; Reaume, Michael; Rhodes, Emily; Knight, Braden; Prud’homme, Denis; Tanuseputro, Peter (BMC Geriatrics, 2020)
Background Hospitalizations carry considerable risks for frail, elderly patients; this is especially true for patients with dementia, who are more likely to experience delirium, falls, functional decline, iatrogenic complications, and infections when compared to their peers without dementia. Since up to two thirds of patients in long-term care (LTC) facilities have dementia, there is interest in identifying factors associated with transitions from LTC facilities to hospitals. The purpose of this study was to investigate the association between dementia status and incidence of hospitalization among residents in LTC facilities in Ontario, Canada, and to determine whether this association is modified by linguistic factors. Methods We used linked administrative databases to establish a prevalent cohort of 81,188 residents in 628 LTC facilities from April 1st 2014 to March 31, 2017. Diagnoses of dementia were identified with a previously validated algorithm; all other patient characteristics were obtained from in-person assessments. Residents’ primary language was coded as English or French; facility language (English or French) was determined using language designation status according to the French Language Services Act. We identified all hospitalizations within 3 months of the first assessment performed after April 1st 2014. We performed multivariate logistic regression analyses to determine the impact of dementia and resident language on the incidence of hospitalization; we also considered interactions between dementia and both resident language and resident-facility language discordance. Results The odds of hospitalization were 39% lower for residents with dementia compared to residents without dementia (OR 0.61, 95% CI 0.57–0.65). Francophones had lower odds of hospitalization than Anglophones, but this difference was not statistically significant (OR 0.91, 95% CI 0.81–1.03). However, Francophones without dementia were significantly less likely to be hospitalized compared to Anglophones without dementia (OR 0.71, 95% CI 0.53–0.94). Resident-facility language discordance did not significantly affect hospitalizations. Conclusions Residents in LTC facilities were generally less likely to be hospitalized if they had dementia, or if their primary language was French and they did not have dementia. These findings could be explained by differences in end-of-life care goals; however, they could also be the result of poor patient-provider communication.

Processus de développement d’une trousse d’accompagnement pour l’examen médical des nouveaux arrivants francophones : un exemple de coopération - Sanou, Boroma; Beaudoin, Monique; Gauthier, Alain P.; Chomienne, Marie-Hélène; Prud’homme, Denis; Kpazaï, Georges (Revue de la Diversité de la Recherche en Santé, 2020)
While over the half of Francophone immigrants living in Ontario come from Africa and the Caribbean, Canadian-trained health professionals are not sufficiently familiar with the health problems that newcomers may face. With this in mind, in a multi-disciplinary partnership, the Center for Rural and Northern Health Research, the Centre de santé communautaire du grand Sudbury, l’Institut du savoir Montfort, the School of Human Kinetics at Laurentian University, and a group of French-speaking immigrants from the City of Greater Sudbury, developed using a collaborative research approach, a newcomer’s medical examination toolkit for health professionals and social services. The toolkit development process involved several steps: 1) establishing a partnership between the above-mentioned organizations; 2) literature review to identify the most common health problems; 3) selection of the most common problems that are not necessarily those that health professionals encounter in everyday practice; 4) writing of draft versions with emphasis on some important aspects of the disease; 5) validation of the fact sheets by the partners; 6) the restitution of the final fact sheets (25 fact sheets including 3 on the general examination, 10 related to certain tropical diseases, 8 sheets related to the signs and symptoms most frequently encountered by health professionals and the other 4 on health care in Ontario); and 7) the development of a digital infograph to ensure greater visibility of the Toolkit for the medical examination of Francophone newcomers.

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Centre de recherche en santé dans les milieux ruraux et du nord, 2020)
fs-ref-orig: Sanou, B., Gauthier, A. P., Hien, A., Michel, I. et Timony, P. (2020). Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Centre de recherche en santé dans les milieux ruraux et du nord. fs-code-orig: Sanou-2020b

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Principaux résultats du rapport technique - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Santé Canada et Consortium national de formation en santé - Volet Larentienne et Volet Boréal, 2020)
fs-ref-orig: Sanou, B., Gauthier, A. P., Hien, A., Michel, I. et Timony, P. (2020). Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Principaux résultats du rapport technique. Santé Canada et Consortium national de formation en santé - Volet Larentienne et Volet Boréal. fs-code-orig: Sanou-2020c

Données sur les soins de longue durée en français-Équipe Santé Ontario du Grand Fleuve - Santé Ontario; Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada (2022)
fs-ref-orig: Santé Ontario, Réseau des services de santé en français de l'Est de l'Ontario et Santé Canada. (2022). Données sur les soins de longue durée en français : équipe Santé Ontario du Grand Fleuve [infographie]. fs-code-orig: Santé Ontario-2022a

Challenges faced by bilingual stroke survivors in the healthcare system: Unique considerations - Sauvé-Schenk, Katrine; Dubouloz-Wilner, Claire-Jehanne; Egan, Mary; Kristjansson, Elizabeth (Linguistic Minorities and Society, 2020)
The experiences of multilingual patients communicating with unilingual healthcare providers have been largely unexplored. The aim of this study was to investigate the experiences of bilingual stroke patients within the Canadian healthcare context. A secondary analysis was completed with data from a multiple case study of the experiences of seven, low-income bilingual Francophone stroke survivors living in a predominately English area. Data included semi-structured interviews, chart reviews and language proficiency assessments. Results demonstrated that bilingual survivors experience unique challenges, including limited French health vocabulary, use of non-standard French, and generally low health literacy levels in both languages. Participants with aphasia often used English and French interchangeably, leading to the potential for miscommunication when providers were not bilingual. The study highlights the importance of having bilingual healthcare providers when bilingual stroke survivors have communication or cognitive limitations. Keywords: Stroke, language, bilingualism, healthcare, literacy

Implementing Active Offer of Services in Both Official Languages in a Hospital Setting in Ontario - Sauvé-Schenk, Katrine; Savard, Jacinthe; Durand, François (Healthcare Policy, 2024)
Providing services in a patient's preferred language is linked to safe and quality care. This paper presents the process and outcomes of implementing practices of active offer (AO) of French-language services in a hospital setting in a region of Ontario with a low density of francophones. Participating unit managers and site coordinators selected AO practices and carried out an implementation plan. The implementation's success was linked to the support received from higher management and site coordinators. Challenges included the managers' rival priorities and perceived language priorities. This process could be applied to meet the needs of other language communities.

Conditions gagnantes pour une offre active de services en français efficace dans un milieu à faible densité de francophones : résultats d’une étude pilote. Rapport sommaire présenté à la Société Santé en français - Sauvé-Schenk, Katrine; Savard, Jacinthe; Prud’homme, Denis; Durand (Chiocchio), F.; Delluc, C. (Institut du savoir Montfort et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)
fs-ref-orig: Sauvé-Schenk, K., Savard, J., Prud’homme, D., Durand (Chiocchio), F. et Delluc, C. (2021). Conditions gagnantes pour une offre active de services en français efficace dans un milieu à faible densité de francophones : résultats d’une étude pilote. Rapport sommaire présenté à la Société Santé en français. Institut du savoir Montfort et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire. fs-code-orig: Sauvé-Schenk-2021

Structural facilitators and barriers to access to and continuity of French-language healthcare and social services in Ontario’s Champlain region - Savard, Jacinthe; Bigney, Kte; Kubina, Lucy-Ann; Savard, Sébastien; Drolet, Marie (Healthcare Policy, 2020)
Purpose: The purpose of this article is to examine access to and continuity of French-language healthcare and social services in Ontario's Champlain region through an analytical framework that incorporates people seeking care, their caregivers and the linguistic component of care into a health and social service system bounded by community, organizational, political and symbolic structures. Methods: Experiences of French-speaking seniors seeking care and those of health and social service providers and managers from two qualitative exploratory studies are used to describe trajectories through the system. Results: Participants exposed how, together with community vitality, issues within each of the system's symbolic, political or regulatory and organizational structures influence these trajectories. Conclusions: To meet the needs of francophone seniors, additional work is needed to increase French-language services coordination within the organizational, regulatory and policy structures of the health and social service system.

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)

Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., & Kubina, L.A. (2021, updated 2025). Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario). In: GReFoPS. Directory of Innovative Practices in Health and Social Services in Official Language Minority Contexts. https://www.grefops.ca/directory_innovative_practices.html fs-code-orig: Savard-2025b

Pratique # 10 : Les points de service satellites (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021). Pratique # 10 : Les points de service satellites (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/ repertoire_pratiques_novatrices.html fs-code-orig: Savard-2021d

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021, mise à jour 2025). Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Savard-2025g

Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021, mise à jour 2025). Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_ pratiques_novatrices.html fs-code-orig: Savard-2025h

Pratique # 14 : Les Foires d’information de la Fédération des aînés et des retraités francophones de l’Ontario (FARFO) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, - Savard, Sébastien; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; de Moissac, Danielle; Durand, François; Dupuis-Blanchard, Suzanne (2024)
fs-ref-orig: Savard, S., Savard, J., Benoît, J., Sauvé-Schenk, K., de Moissac, D., Durand, F., Dupuis-Blanchard, S. (2024). Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS), Université d'Ottawa. fs-code-orig: Savard-2024d

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada

A self-assessment tool for healthcare and social service provision in French: What use for managers? - Savard, Sébastien; Savard, Jacinthe; van Kemenade, Solange; Benoît, Josée; Tabor, Michelle (Healthcare Management Forum, 2020)
Language is an important determinant of health, and lack of access to quality, linguistically adapted healthcare and social services negatively impacts users. Besides the lack of bilingual resources, our previous research on Francophone minority community seniors’ trajectories through these services shed light on important and nonobvious challenges currently faced by organizations offering healthcare and social services to this population. Current service provision appeared limited due to organizations working in silos with suboptimally used resources for integrating active offer of French language services throughout the continuum of care. This situation led our team to create the Organizational and Community Resources Self-Assessment Tool for Active Offer and Continuity of French Language Healthcare and Social Services, which is intended to help managers and service providers promote and facilitate the integration of active offer throughout the continuum of service provision. This article describes the Tool’s creation, content validation, and pilot-testing.

Contributions d’OZi à l’état des lieux des services de santé en français en Ontario. - Scullion, David; Taillon, Myriam; Ranger, Marie-Christine; Glaude, Normand; Desaulniers, Jacinthe (Minorités linguistiques et société, 2024)
Entre 2017 et 2020, l’organisme OZi a effectué la collecte et l’analyse de données sur les services de santé en français à l’échelle de la province, dans le cadre de la Loi sur les services en français de l’Ontario. Les résultats de cette recherche descriptive et exploratoire portent sur la répartition géographique de l’offre des services de santé en français, le continuum de soins, les exigences de la désignation et les ressources humaines possédant des capacités linguistiques en français. Ces résultats permettent de dresser l’état des lieux des services de santé en français en Ontario, en mettant en lumière les points forts comme les lacunes des services de santé en français. Les résultats sont discutés sous l’angle de l’accès et la planification des services de santé en français ainsi que celui de la performance de la désignation. Mots-clés : santé, offre active, Ontario, désignation des fournisseurs de santé, continuum de soins

Patient-physician language concordance and quality and safety outcomes among frail home care recipients admitted to hospital in Ontario, Canada - Seale, Emily; Reaume, Michael; Batista, Ricardo; Eddeen, Anan. Bader; Roberts, Rihannon; Rhodes, Emily; McIsaac, Daniel. I.; Kendall, Claire. E.; Sood, Manish. M.; Prud'homme, Denis; Tanuseputro, Peter (Canadian Medical Association Journal, 2022)
Background: When patients and physicians speak the same language, it may improve the quality and safety of care delivered. We sought to determine whether patient–physician language concordance is associated with in-hospital and postdischarge outcomes among home care recipients who were admitted to hospital. Methods: We conducted a population-based study of a retrospective cohort of 189 690 home care recipients who were admitted to hospital in Ontario, Canada, between 2010 and 2018. We defined patient language (obtained from home care assessments) as English (Anglophone), French (Francophone) or other (allophone). We obtained physician language from the College of Physicians and Surgeons of Ontario. We defined hospital admissions as language concordant when patients received more than 50% of their care from physicians who spoke the patients’ primary language. We identified in-hospital (adverse events, length of stay, death) and post-discharge outcomes (emergency department visits, readmissions, death within 30 days of discharge). We used regression analyses to estimate the adjusted rate of mean and the adjusted odds ratio (OR) of each outcome, stratified by patient language, to assess the impact of language-concordant care within each linguistic group. Results: Allophone patients who received language-concordant care had lower risk of adverse events (adjusted OR 0.25, 95% confidence interval [CI] 0.15–0.43) and in-hospital death (adjusted OR 0.44, 95% CI 0.29–0.66), as well as shorter stays in hospital (adjusted rate of mean 0.74, 95% CI 0.66–0.83) than allophone patients who received language-discordant care. Results were similar for Francophone patients, although the magnitude of the effect was smaller than for allophone patients. Language concordance or discordance of the hospital admission was not associated with significant differences in postdischarge outcomes.

Le vieillissement francophone en contexte minoritaire. Défis et opportunités - Siméon, Frantz; Couturier, Yves (Reflets, 2021)

Agir ensemble pour une Petite enfance en santé dans les communautés francophones et acadienne en situation minoritaire : Résultats et impacts du programme Petite enfance en santé 2024-2025 - Société Santé en français et les Réseaux de santé en français (2025)

Enjeux et complexité de la démence en milieu rural francophone : regards sur les réalités familiales [mémoire de maîtrise, Université d'Ottawa] - Sullivan, Cassidy (Université d'Ottawa, 2020)
Les personnes aînées se retrouvent parmi les groupes les plus susceptibles d’être diagnostiqués d’une maladie cognitive, telle qu’une démence. La réception du diagnostic est un événement bouleversant pour toutes les personnes impliquées, et plus particulièrement pour les familles. Dans la région d’Ottawa, il existe une variété de ressources pour soutenir les personnes atteintes d’une démence ainsi que leurs proches. Or, la littérature disponible indique que les personnes francophones vivant dans un milieu rural ne vivent pas la même réalité (Forgues, Doucet et Guignard (2011). Bien que les impacts de la démence sur les relations familiales pourraient varier d’un endroit à un autre, l’emplacement et la disponibilité des services francophones jouent également un rôle important dans le parcours de ces personnes. Ces facteurs nous invitent à poser la question suivante : Quels sont les impacts de la démence sur la dynamique familiale et l’accès aux services francophones des personnes vivant dans un milieu rural ? À partir de la perspective d’intervenantes sociales, l’étude a permis : 1) d’explorer les réalités et enjeux vécus par les familles lors de la réception d’un diagnostic de démence, comme la maladie d’Alzheimer, chez un proche âgé vivant dans un contexte rural francophone ; 2) d’examiner les défis d’accès aux services rencontrés par les aidants familiaux, et finalement ; 3) de comprendre les réalités des familles lors de la progression de la maladie. Cette recherche a été menée dans les Comtés unis de Prescott-Russell, une région bilingue de l’est de l’Ontario. Dans cette étude, nous avons identifiés le vécu des familles suite à la réception d’un diagnostic de démence, ainsi que les ressources disponibles pour les personnes de cette région qui sont touchées par la maladie. En ce qui trait au cadre conceptuelle et théorique choisi pour cette étude, nous avons optés pour l’épreuve relationnelle et l’approche écosystémique pour analyser nos thèmes. Sur le plan méthodologique et en se basant sur des entrevues semi-dirigées, cette étude a nécessité la participation de trois intervenantes sociales œuvrant auprès des familles ayant un proche atteint d’une démence, et ce, dans la région de Prescott-Russell. Il ressort principalement des résultats de cette étude que les enjeux observés par les intervenantes sur la gestion de la démence en milieu rural et l’accès aux services sont lié à la navigation entre les services, l’éducation sur la démence et l’optimisation des services de soutien. Ces dernières constatent des points à améliorer en ce qui concerne le discours social sur le vieillissement ainsi que le manque de financement pour l’augmentation de la visibilité et de l’accessibilité des services francophones. Mots clés : Personne aînée, maladie d’Alzheimer, ruralité, francophonie, accessibilité, services adaptés, dynamique familiale

Des services de santé dans ma langue, un “horizon d’attente” : Programme de santé mentale de Montfort et parcours psychiatriques. - Thifault, Marie-Claude (Le moment Monfort dans la francophonie canadienne, 2024)
fs-ref-orig: Thifault, M.-C. (2024). Des services de santé dans ma langue, un “horizon d’attente” : Programme de santé mentale de Montfort et parcours psychiatriques. Dans F. Charbonneau et M. Bock (dir.), Le moment Monfort dans la francophonie canadienne (p. 205-226). Presses de l’Université d’Ottawa. fs-code-orig: Thiffault - 2024

Dérives : une histoire sensible des parcours psychiatriques en Ontario français - Thifault, Marie-Claude; LeBel, Marie (Les Presses de l'Université d'Ottawa, 2021)
fs-ref-orig: Thifault, M.-C. et LeBel, M. (2021). Dérives : une histoire sensible des parcours psychiatriques en Ontario français. Les Presses de l'Université d'Ottawa. fs-code-orig: Thifault-2021

Rethinking the way we measure access to language-concordant health services for minority language populations: a secondary analysis of publicly available physician and population data in Ontario, Canada - Timony, Patrick E.; Belanger, Christopher; Bélizaire, Arlynn; Desilets, Antoine; Gauthier, Alain; Karunananthan, Sathya; Muray, Mwali-Nachishali; Peixoto, Cayden; Fitzsimon, Jonathan Peter; Godfrey, Leanda; Bjerre, Lise M. (BMJ Open, 2025)
Abstract Objective Providing care in a patient’s preferred language improves health outcomes and patient satisfaction. In Ontario, access to French-speaking physicians (FSPs) is estimated using FSP-to-Francophone population ratios and compared with total physician-to-total population ratios. This approach fails to consider the fact that FSPs also serve non-Francophone patients and that Francophones must compete with the entire population to access FSPs. As a result, this approach inaccurately suggests that Francophones have better access to language-concordant care than Anglophones/Allophones. We propose a novel approach to address this issue, enabling unbiased comparisons of access to language-concordant care across linguistic groups. Design This secondary analysis of publicly available data containing linguistic variables for the Ontario population (Statistics Canada, 2021 Census) and for family physicians (FPs) (College of Physicians and Surgeons of Ontario, January 2024) calculated competition-adjusted ratios and probabilities of accessing language-concordant care. Setting Ontario, Canada. Participants Census and publicly available data on FPs (ie, those providing comprehensive family medicine care to the community) and the Ontario population were obtained. Results Province-wide, the crude ratio of FSPs per 1000 Francophones was 3.46. After adjusting for competition, the ratio of FSP per 1000 population was 0.12, compared with a general physicians-per-1000 population ratio of 1.05. Anglophones/Allophones attached to a FP have a 100% probability of receiving care in English compared with an 11.4% probability for Francophones to receive care from a FSP. Expressed otherwise, Anglophones/Allophones are 8.8 times more likely to receive language-concordant care (ie, care in English) than Francophones. Conclusions Although crude physician-to-population ratios overestimate Francophones’ access to FSPs, competition-adjusted ratios and probabilities demonstrate that they are much less likely to access language-concordant care than Anglophones/Allophones. This novel approach has equity implications for health human resources planning and can be applied to other linguistic minority groups and healthcare providers.

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

The impact of linguistic concordance and the active offer of French language services on patient satisfaction - Timony, Patrick; Gauthier, Alain; Wenghofer, Elizabeth; Hien, Amelie (Diversity of Research in Health Journal, 2022)
Communication is essential to providing quality primary care. Linguistic concordance between patients and physicians has been linked to improved health outcomes and greater patient satisfaction. Although Canadian Francophones often struggle to access linguistics concordant health services, the concept of the active offer of French Language Services (FLS) has emerged as a means of ensuring the availability of such services and improving the francophone patient experience. However, the impact of language concordance and the active offer of FLS on patient satisfaction among Ontario Francophones remain largely unknown. Patient satisfaction surveys were collected as part of a continuing education program targeted at family physicians in Northeastern Ontario. Participating physicians distributed patient surveys consisting of select patient satisfaction questions from the Physicians Achievement Review (PAR) and select questions from the Active Offer of French Language Services in Minority Context Measure. Valid surveys were received from 235 patients. Just under half of these (44%) identified as Francophones, 62.6% had a French-speaking family physician; however, only 17.2% reported regularly speaking in French with their family physician. As hypothesized, there was a consistent tendency for Francophones who experience stronger linguistic concordance with their family physician to report higher satisfaction scores. Francophones who regularly speak French with their family physicians were more satisfied ( = 4.63) than those who rarely/never speak French ( = 4.29, F(1; 83) = 4.852; p < 0.05). There was also a statistically significant interaction between the patients' language of preference and the service language. Francophones who prefer French and regularly speak it with their family physician (linguistic concordance; adj= 4.82) were significantly more satisfied than those who prefer French yet rarely/never speak it (linguistic discordance; adj= 4.06, F(1; 75) = 11.950; p < 0.001). Furthermore, a positive correlation between patient satisfaction and the active offer was observed in Francophones (r = 0.49, p<0.001). The present findings provide evidence of the impact of linguistically adapted health care services on the satisfaction of Ontario Francophones and suggest that patient satisfaction may be improved through the active offer of FLS. A larger and more diverse sample is required to confirm these findings.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport de synthèse visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport de synthèse en décrit les principaux constats, accompagnés de quelques citations de participants.

Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)
fs-ref-orig: van Kemenade, S., Benoît, J., Savard, S. et Savard, J. (2025). Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_ pratiques_novatrices.html. fs-code-orig: van Kemenade-2025d